1992
DOI: 10.1016/1044-0305(92)87005-j
|View full text |Cite
|
Sign up to set email alerts
|

Are the electrospray mass spectra of proteins related to their aqueous solution chemistry?

Abstract: Institute for Environmental Chemistry, National Research Council of Canada, Ottawa, Ontario, Canada The shape of the profile described by the relative abundances of multiply charged ions of proteins in the electrospray mass spectrum can be described by means of one or more Gaussian functions. An aqueous solution equilibrium model of the distribution of multiply charged ions of equine cytochrome c and myoglobin has been shown to match qualitatively the shape of the distribution of these ions in an electrospray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(68 citation statements)
references
References 40 publications
1
66
0
1
Order By: Relevance
“…Formation of polyanionic species in the negative ion ESI MS usually proceeds via deprotonation of polypeptides. It is the intimate involvement of protons in generating multiply charged ions of biopolymers that led some to believe that the charge state distributions observed in ESI MS must reflect the cumulative charge on the acidic and basic residues in solution [19,20]. In this view, the large-scale conformational dynamics of the polypeptide chains in solution influenced the charge state distributions indirectly, by modulating the pK a values of individual amino acid residues.…”
Section: Can Charge-state Distributions Provide Information On Proteimentioning
confidence: 99%
“…Formation of polyanionic species in the negative ion ESI MS usually proceeds via deprotonation of polypeptides. It is the intimate involvement of protons in generating multiply charged ions of biopolymers that led some to believe that the charge state distributions observed in ESI MS must reflect the cumulative charge on the acidic and basic residues in solution [19,20]. In this view, the large-scale conformational dynamics of the polypeptide chains in solution influenced the charge state distributions indirectly, by modulating the pK a values of individual amino acid residues.…”
Section: Can Charge-state Distributions Provide Information On Proteimentioning
confidence: 99%
“…It was suggested that the ion abundance profiles in ESI-MS might reflect the abundances of preformed, multiply charged species in aquous solution [24]. Therefore a 'snapshot' of the cytochrome c2 wild-type and mutant conformations could be obtained by observing the CSD in the positive ESI mass spectrum, where the number of charges corresponds to the number of ionized basic residues.…”
Section: Probing Cytochrome C: Conformation Using Csdmentioning
confidence: 99%
“…Dramatic new ionization methods for mass spectrometry (MS) have made possible the formation of protein ions in the gas phase to measure molecular weight and primary sequence information (2-4), even on fmol samples (5,6). Recent studies indicate that protein conformations in solution can affect the resulting charge distribution of the gaseous multiply charged ions formed by electrospray ionization (ESI) (7)(8)(9) and that even noncovalent complexes can survive ESI to form gaseous multiply charged ions (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%